2009
DOI: 10.1016/j.jcin.2008.08.022
|View full text |Cite
|
Sign up to set email alerts
|

Attenuated Plaque Detected by Intravascular Ultrasound

Abstract: Attenuated plaque was more common in ACS patients with STEMI than NSTEMI. Attenuated plaque in ACS patients was associated with a higher C-reactive protein level, more severe and complex lesion morphology, reduced coronary blood flow before PCI, and especially no-reflow after PCI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
17
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 119 publications
(18 citation statements)
references
References 39 publications
1
17
0
Order By: Relevance
“…Specifically, lipid-rich fibroatheromas are friable and easily disrupted during PCI, predisposing to periprocedural MI (9). Over the past several years, case reports and uncontrolled or retrospective registries have suggested that plaque characterization by invasive imaging with gray-scale and radiofrequency intravascular ultrasound (IVUS), optical coherence tomography, and near-infrared spectroscopy (NIRS) may identify emboli-prone lesions (10)(11)(12)(13)(14)(15)(16). Moreover, distal protection devices have been shown to prevent embolization and reduce periprocedural myonecrosis after PCI of friable saphenous vein graft lesions (17,18).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, lipid-rich fibroatheromas are friable and easily disrupted during PCI, predisposing to periprocedural MI (9). Over the past several years, case reports and uncontrolled or retrospective registries have suggested that plaque characterization by invasive imaging with gray-scale and radiofrequency intravascular ultrasound (IVUS), optical coherence tomography, and near-infrared spectroscopy (NIRS) may identify emboli-prone lesions (10)(11)(12)(13)(14)(15)(16). Moreover, distal protection devices have been shown to prevent embolization and reduce periprocedural myonecrosis after PCI of friable saphenous vein graft lesions (17,18).…”
mentioning
confidence: 99%
“…Quantitative IVUS measurements included external elastic membrane (EEM) cross-sectional area, plaque and media (EEM minus lumen) cross-sectional area, plaque burden (plaque and media divided by EEM cross-sectional area), and minimal lumen area (MLA).Measurements were taken both at the site of the MLA within the entire lesion and at the MLA site within the maxLCBI 4mm segment. Attenuated plaque was defined as hypoechoic plaque with deep ultrasound attenuation without calcification or very dense fibrous plaque(12). The same core laboratory determined the LCBI, maxLCBI 4mm , and the lipid-rich plaque burden, defined as the proportion of plaque-containing lipid (OnlineFigure 2).…”
mentioning
confidence: 99%
“…This finding has been termed "attenuated plaque" and has been considered an IVUS characteristic of high-risk lesions (2)(3)(4). The concept that attenuated plaque is an exclusive marker of lesion instability is supported by recent data showing absence of attenuation at the lesion sites causing stable coronary syndromes (5), and could have therapeutic implications in the setting of percutaneous coronary intervention (4). However, to understand the significance of "attenuation," it is important to investigate its presence and frequency in stable, nonculprit lesion sites.…”
mentioning
confidence: 99%
“…Lee et al (42) reported that attenuated plaque, defined as hypoechoic plaque not due to calcium shadowing and considered to represent necrotic core by gray-scale IVUS, was never found in stable patients, but was observed in 39.9% of patients with ST-segment elevation MI, supporting the association of attenuated plaque with necrotic-core plaque and/or a platelet thrombus. In contrast, Bayturan et al (43) found that attenuated plaques were found with equal frequency in stable and unstable patients and not associated with subsequent coronary events.…”
Section: Detection Of the Necrotic Corementioning
confidence: 98%